Perbandingan Teknik Aplikatif Cat Eyes Eyeliner dengan Winged Eyeliner pada Tata Rias Pengantin Muslim untuk Bentuk Mata Bulat - Putri, Adillah Amirul; Lutfiati, Dewi (Journal of Beauty and Cosmetology (JBC), 2021)
Eyeliner is a cosmetic that is commonly used on the eye line to emphasize the eye line. The use of eyeliner can also manipulate the shape of the eyes so that the eyes will look more beautiful and defined. Applying the right eyeliner can also minimize the use of lashes to emphasize the shape of the eye. This study aims to (1) determine the results of the comparison of the applied techniques of cat eye eyeliner with winged eyeliner in Muslim bridal make-up for round eyes (2) to find out which applied eyeliner techniques have the overall results make round eyes look neat, proportional and firm. This type of research is experimental research. The subjects in this study were applied techniques of cat eyes eyeliner with winged eyeliner on Muslim bridal make-up for round eye. The data collection method used was observations made by 34 respondents. The data analysis technique used is the Independent Sample T-Test. The results showed that the application of cat eyes eyeliner and winged eyeliner to Muslim bridal make-up for round eyes did not have a significant difference. The best result in this study is the applied winged eyeliner technique. The average result of the applied winged eyeliner technique has the highest score on three aspects of assessment, namely the proportion of the eye shape of 3.3, the aspect of eye firmness of 3.6, and the overall result of eye makeup of 3.5.Keywords: make-up, cat eyes eyeliner, winged eyeliner, round eyes